Thermal and Humidity Conditions Over a Salient Land Form as Exemplified by a Coastal Sand Dune at the Łeba Sandbar in the Słowiński National Park - Kolendowicz, Leszek; Forycka-Ławniczak, Hanna (Quaestiones Geographicae, 2013)
In July 2011, measurements were taken of selected meteorological elements in the central part of the Łeba Sandbar in the Słowiński National Park. On the basis of the results of measurements performed at five points located on a salient land form in close proximity to the seashore, a thermal and humidity characteristics of this form were determined for a twenty-four hour period. The results of measurements obtained from an automatic weather station located in an open area, near the measurement points on the coastal sand dune, were used as information on the atmospheric conditions predominant in the standard area (flat area covered by grass). The research analysis was performed for the entire measurement period and for days with radiational weather. The authors also determined the dependence between air temperature and humidity values observed over the analysed land form and the values of weather elements measured over the standard area.